A study on the ways of efficiency of lead time in apparel merchandising in Versatile Apparel Private Limited - Imtiaz, Md. Nakib (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.